The Influence Hedonic Shopping Motivation and Positive Emotions On Online Implusive Buying Of Shopee Application Users - Giovanni, Erick Hardian; Handriana, Tanti (Universitas Syiah Kuala, 2024)
Flash sale has become a very popular strategy because it effectively attracts consumer interest and increases sales. Flash sale promotions have a strong relationship with impulsive buying. This study aims to analyze the effect of Hedonic Shopping Motivation on Online impulse buying through Positive Emotions. The research method used in this study is a quantitative approach. The objects of this study were 30 Shopee users using the purposive sampling method. Hypothesis testing was analyzed using PLS analysis. The results of this study show that hedonic shopping motivation significantly affects positive emotions and online impulse buying, and positive emotions have a substantial effect on online impulse buying.